2008
DOI: 10.1152/ajpendo.90287.2008
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious action of FA metabolites on ATP synthesis: possible link between lipotoxicity, mitochondrial dysfunction, and insulin resistance

Abstract: Insulin resistance is a characteristic feature of type 2 diabetes and obesity. Insulin-resistant individuals manifest multiple disturbances in free fatty acid (FFA) metabolism and have excessive lipid accumulation in insulin target tissues. Although much evidence supports a causal role for altered FFA metabolism in the development of insulin resistance, i.e., "lipotoxicity", the intracellular mechanisms by which elevated plasma FFA levels cause insulin resistance have yet to be completely elucidated. Recent st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 54 publications
8
86
0
Order By: Relevance
“…In addition to the change in substrate availability, which is an important regulator of mitochondrial activity, removal of intracellular metabolites that could influence mitochondrial activity could also alter mitochondrial metabolism. For example, we have shown previously that elevated concentrations of fatty acyl Co-A inhibit oxidative phosphorylation in skeletal muscle mitochondria, and an increased level of intracellular fatty acyl Co-A has been reported in both type 2 diabetic and obese non-diabetic insulin-resistant individuals compared with lean insulin-sensitive participants [21]. Thus, mitochondrial metabolism measured in vivo may differ from that measured ex vivo.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition to the change in substrate availability, which is an important regulator of mitochondrial activity, removal of intracellular metabolites that could influence mitochondrial activity could also alter mitochondrial metabolism. For example, we have shown previously that elevated concentrations of fatty acyl Co-A inhibit oxidative phosphorylation in skeletal muscle mitochondria, and an increased level of intracellular fatty acyl Co-A has been reported in both type 2 diabetic and obese non-diabetic insulin-resistant individuals compared with lean insulin-sensitive participants [21]. Thus, mitochondrial metabolism measured in vivo may differ from that measured ex vivo.…”
Section: Discussionmentioning
confidence: 95%
“…Mitochondrial purification Mitochondria were purified from muscle tissue as previously described [21]. Mitochondrial integrity was assessed by respiratory control ratio (>6 with pyruvate) at the end of each experiment.…”
Section: Methodsmentioning
confidence: 99%
“…Reports showing that the flux of the TCA cycle was reduced in type 2 diabetes and that an enhanced mitochondrial metabolism accounted for adaptation of beta cells to high-fat diet-induced insulin resistance [40,41] support that appropriate oxidation metabolism is essential for maintenance of cell viability in HG/PA-exposed beta cells. In addition to an insufficient supply of fuel substrates, it was reported that the ATP synthesis process was impaired in FFA-treated cells [42,43] and expression of the molecules related to energy metabolism were decreased in islets of diabetic subjects [44]. Collectively, energy-producing metabolism is impaired in HG/PA-treated cells, which may explain the induction of beta cell glucolipotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…24 Recent studies have revealed that the accumulation of IMCL intermediates might impair insulin signaling 25 and the mitochondrial function. 26 Therefore, IMCL might have a major role in the pathogenesis of insulin resistance.…”
Section: Control Metsmentioning
confidence: 99%